Abstract WMP53: Sex Differences n Long-term Mortality and Disability After Stroke: The International Stroke Outcomes Study - Phan, Hoang T; Reeves, Mathew J; Blizzard, Leigh; Thrift, Amanda; Cadilhac, Dominique; Heeley, Emma; Sturm, Jonathan; Gall, Seana (Stroke (1970), 2016)
Abstract only Introduction: It is uncertain why women suffer worse long-term outcomes after stroke than men. We examined sex differences in mortality and disability 1 and 5 years after stroke and identified factors contributing to these differences. Methods: Individual patient data pooling study of incident strokes (ischemic and hemorrhagic) from 1987-2013 obtained from 12 population-based cohorts from Australasia, Europe, South America and the Caribbean. Data on socio-demographics, stroke-related factors and pre-stroke health were obtained for each patient and harmonized between studies. Poisson modelling estimated the mortality rate ratio (MRR) for women compared to men at 1 year (12 studies) and 5 years (7 studies) post-stroke. Log binomial regression estimated the relative risk (RR) of poor outcome (modified Rankin scale>2 or Barthel Index <20) for women compared to men at 1 year (9 studies) and 5 years (6 studies) after stroke. Multivariable models were adjusted for potential confounders including age, pre-stroke dependency, stroke severity and comorbidities. Results: A total of 16557 first-ever-stroke patients with follow-up data to 1 year and 12,839 with follow-up to 5 years were included. The pooled crude mortality was greater in women than men at 1-year (MRR 1.37 95% CI 1.27-1.48) and 5 years (MRR 1.25 95% CI 1.13-1.39). However, these sex differences were reversed after adjustment for confounders at both 1 year (MRR 0.94 95% CI 0.82-1.06) and 5-years post stroke (MRR 0.74 95% CI 0.66-0.84). Similarly, the pooled crude RR for disability after stroke was greater in women than men at 1-year (RR 1.28 95% CI 1.17-1.39 and 5-year (RR 1.32 95% CI 1.18-1.47), but these sex differences disappeared after adjustment at both 1 year (RR 1.08 95%CI 0.98-1.18) and 5-years post stroke (RR 1.08 95% CI 0.97-1.20). The key contributors to worse outcomes in women were greater age, pre-stroke dependency, severe strokes and atrial fibrillation (AF, mortality only) compared with men. Conclusion: Worse outcomes in women were mostly due to age and potentially modifiable factors of stroke severity and AF providing potential targets to reduce the impact of stroke in women.